Susceptibility of Bacterial Isolates From Wound Swabs in Bangladesh: Laboratory – Based Surveillance Study - Iqbal, Hasina; Ahmed, Mushtaque; Mahboob, Nabeela; Afrin, Sabrina; Mamun, Kazi Zulfiquer (Journal of Dhaka Medical College, 2023)
Background: Wound infection is one of the major health problems that occur frequently. Infections of the wound result from entry of the organisms through breached skin. It plays an important role in the development of chronicity, delaying wound healing. It is evident that wound infection is a challenging situation for the physicians. Multiple bacteria can cause wound infection. Both broad spectrum and narrow spectrum antibiotics are available for the treatment. It is ideal to give proper antibiotic after culture and sensitivity of the wound swab. Improper and irrational use of antibiotics can lead to drug resistance. Objective: To isolate and identify the bacteria causing wound infection and to determine the antimicrobial susceptibility pattern. Materials and method: This descriptive cross-sectional study was carried out at the Microbiology Laboratory, Popular Diagnostic Centre Ltd, Dhanmondi, Dhaka, Bangladesh, from November 2019 to January 2020. A total of 62 wound swabs were collected and analyzed for culture and antibiotic sensitivity. Results: From total wound swab samples, 49 (79%) were culture positive. The most common isolated pathogen was Acinetobacter spp. 20 (40.81%). Other isolates were Staphylococcus aureus 10 (20.41%); Escherichia coli 07 (14.29%); Pseudomonas aeruginosa 07 (14.29%); Klebsiella 04 (08.16%) and Proteus 01 (02.04%). Among the Gram negative isolates, Acinetobacter spp showed 100% sensitivity to colistin, 85% to imipenem, 30% to amikacin and 25% to piperacillin + tazobactum. E. coli showed 100% sensitivity to imipenem and colistin and least sensitivity to third generation cephalosporin. Pseudomonas showed 100% sensitivity to piperacillin+tazobactum, 85.71% to imipenem and aztreonam. Among the Gram positive isolates, Staphylococcus aureus showed 100% sensitivity to linezolid, vancomycin, imipenem, cloxacillin, amikacin and least sensitivity to azithromycin. Conclusion: Acinetobacter spp. was the most frequently isolated pathogen from wound swab and the antibiotic sensitivity pattern of various isolates will help the clinician in appropriate selection of antibiotics against wound infection. J Dhaka Med Coll. 2021; 30(2) : 180-188